Industrial Structure, Demographic Pattern, and Indonesian Current Account - Ni Putu Wiwin Setyari; Ida Bagus Putu Purbadharmaja; Ni Luh Karmini (Universitas Hayam Wuruk Perbanas, 2016)
The new trade theory shows the interaction between capital intensity, reflects the comparative advantages of a country as well as the industrial structure, and international capital flows. One main proposition stated if a country has high capital intensity in their industrial structure, and changes tends to be capital intensive, foreign capital will flow into the country because the domestic savings position become lower than investment needs. It can explain why international capital flows from developing countries to the developed countries that are relatively rich in capital. This study attempted to examine the consistency and reliability of the theory in the context of Indonesia. The important thing here is the existence of different viewpoints in assessing the phenomenon of the current account balance. The model used is the restricted error correction mechanism in Autoregressive Distributed Lag (ECM-ARDL) approach. The result indicates that both industrial structure and demographic pattern are affecting Indonesian current account significantly. Specifically, capital intensity negatively affects Indonesian current account. This indicates the higher capital intensity, which means the greater tendency to capital-intensive industry structure, leads to higher current account deficit. The analysis also highlights the importance of demographic pattern in determines Indonesian current account through their impact to savings – investment position.